Exploring successes and failures of the CEEC in the context of the EU accession. The milk and beef sectors in the Czech Republic and Poland - Miroslava Bavorova; Heinrich Hockmann; Agata Pieniadz (Agricultural Economics (Zemědělská ekonomika), 2004)
The paper reviews experiences from the accession process of Poland and the Czech Republic, two countries with different accession conditions regarding the agri-food sector. The paper has two main aims. First is to discuss the scope of action in the EU and in the acceding countries from a game theoretical view. The second aim is to identify the reasons for successfully providing beneficial accession criteria. Investigating two selected agricultural sectors does this: milk and beef production. Our overall argument is that the actions, which nations and interest groups have undertaken with regard to the EU accession and future policy direction are, at least partially, a function of different external restrictions and internal national patterns; i.e., the relevance and structure of agriculture and the bargaining power of interest groups. – – Příspěvek se zabývá procesem přístupu Polska a České republiky, zemí s významnými rozdíly zemědělsko-potravinářského komplexu. Hlavním cílem článku je analýza podmínek a omezení jednání jak ze strany EU, tak i ze strany přistupujících zemí z pohledu teorie her a posouzení dojednaných podmínek vstupu na příkladu produkce mléka a hovězího masa. Analýza ukázala, že přístupová jednání byla determinována jak vnějšími podmínkami zúčastněných států jako např. WTO závazky, tak i vnitřními podmínkami jednotlivých států jako např. strukturou zemědělství a tlakem oborových svazů.
Keywords: 330; accession process; interest groups; Copenhagen agreement; integrační proces; oborové svazy; Smlouva o přistoupení